Evaluation of Tip Surface Collision Count as a Measure of Fibreoptic Scope Handling Skills: A Randomized, Cross-Over Manikin Study. (2nd October 2014) - Roberts, Mari H.; Boucher, Elizabeth K.; Lim, Michael; Wilkes, Antony R.; Hodzovic, Iljaz
Abstract : Background . In this pilot study, we evaluated tip collisions against three commonly used measures of fibreoptic scope handling skills. Methods . Seventy-seven anaesthetists were recruited to perform a standardized task on an Oxford Box and a modified AirSim manikin. Collision count was correlated against time to scope placement, a global rating scale score, and up-to-date fibreoptic experience. Results . Strong and moderate correlations were found between collision count and task completion time for the Oxford Box ( ρ = 0.730, P < 0.0001) and AirSim manikin ( ρ = 0.405, P < 0.0001), respectively. Moderate correlation was found between collision count and global rating scale score for the Oxford Box ( ρ = −0.545, P < 0.0001) and AirSim manikin ( ρ = −0.500, P < 0.0001). Mild and moderate correlations were found between collision count and fibreoptic experience on the Oxford Box ( ρ = −0.240, P = 0.041) and AirSim manikin ( ρ = −0.423, P < 0.0001), respectively. Conclusions . This study infers that collision count may be used as a measure of fibreoptic scope handling skills in simulation training. Using this outcome in addition to other measures of performance may improve accuracy and precision of fibreoptic scope placement.